DEVELOPMENT OF A FINANCIAL AND RISK MANAGEMENT SELF-AUDIT MODEL BASED ON CONTINGENCY THEORY TO EMPOWER SMALL AND MEDIUM-SIZED ENTERPRISES - Nul Khayril Haziqah Binti Azmi; Nurul Labanihuda Binti Abdull Rahman; Noor Hafizha Binti Muhamad Yusuf; Nadhilah Binti Abdul Pisal; Norziana Binti Yahya; Rabeatul Husna Binti Abdull Rahman (Journal of Islamic, Social, Economics and Development, 2024)
Inadequate financial management is the main cause of entrepreneurs' inability to successfully run a company. A crucial component of company management for small and medium-sized enterprises (SMEs) is financial management. It is believed that this industry is one of the revenue streams that stimulate the nation's economic growth. In order to help businesses handle financial resources more methodically, the nation truly needs businesspeople with a competitive understanding of financial management. Nonetheless, the findings of earlier research indicate that SME owners are under a concerning amount of financial strain. The reason behind the inadequate management of received information is a deficient management accounting system. In actuality, there has been a long-term effect on corporate performance due to the underutilization of certification management techniques like budgeting, performance management tools, and tracking tools. This study proposes three main objectives. The first objective is to determine the elements that make conducting business risky. Analysing SMEs' financial and risk management strategies is objective number two. The ultimate goal is to create a contingency theory-based self-audit risk and financial management model for small and medium-sized businesses. This study employs a qualitative research design. To fulfil the study's initial goal, a review of relevant literature and respondent interviews were used to gather data on financial issues that SMEs face. Additionally, empirical research was carried out on a limited number of financial institutions, specifically Amanah Ikhtiar in order to gather data on completed actions in a number of designated zones. The Shared Prosperity Vision (WKB) 2030 aims to develop the economy and support key economic growth activities (KEGA) by boosting financial management among B40 entrepreneurs. Hence, these results might serve as a roadmap for stakeholders and help them overcome these challenges.